Improving seed potato quality in Ethiopia: a value chain perspective - Hirpa Tufa, A.; Meuwissen, M.P.; Lommen, W.J.; Oude Lansink, Alfons G.; Tsegaye, A.; Struik, Paul C. (Wageningen University & Research, 2016)
In Ethiopia, use of low-quality seed potatoes by the majority of potato growers is associated with underdevelopment of the seed potato value chains. Three seed potato systems are present in Ethiopia: the informal seed system, the alternative seed system and the formal seed system. This chapter analyses the performance of seed potato value chains with respect to their ability to supply quality seed tubers to seed potato systems, by using the chain performance drivers enabling environment, technology, market structure, chain coordination, farm management, and inputs. Information obtained from literature review, secondary data and key informants’ interviews were used for the analysis. In the informal seed system, seed potato value chains suffered from a poor enabling environment such as a low quality technical support and lack of a seed quality control system; use of sub-optimal storage and transportation technologies, sub-optimal farm management practices; and little use of inputs. In the alternative seed system, main constraints were the lack of a seed potato quality control system, poor farm management practices, little use of inputs by seed potato growers, and a distorted seed potato market that resulted from involvement of institutional buyers. Chains in the formal seed potato system were characterised by little involvement of the private and public sectors in the production and supply of seed potatoes. Based on the analysis, improvement options for the three seed systems were identified.